Clinical characteristics of patients with heart failure and intracardiac thrombus - Zhai, Mei; Huang, Liyan; Liang, Lin; Tian, Pengchao; Zhao, Lang; Zhao, Xuemei; Huang, Boping; Feng, Jiayu; Huang, Yan; Zhou, Qiong; Zhang, Yuhui; Zhang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure (HF) patients are in a hypercoagulable state that predisposes to intracardiac thrombus. We aim to assess clinical features of patients with HF and intracardiac thrombus. Methods: Patients diagnosed as HF with intracardiac thrombus were enrolled in this study. Patients’ demographics, clinical comorbidities, laboratory tests and cardiac imaging parameters were recorded. Baseline characteristics were described, relationship between intracardiac thrombus location and cardiac underlying diseases, New York Heart Association (NYHA) class and left ventricular ejection fraction (LVEF) were analyzed, and anticoagulation were summarized. Results: A total of 1,248 patients were included in the study. Most patients were male (72.2%) with a mean age of 54 years. Left ventricle is the most frequently involved (66.8%) and left ventricular thrombus is more prevailing in patients complicated with coronary artery diseases, ventricular noncompaction cardiomyopathy and dilated cardiomyopathy (86.3%, 86.4% and 78.2%, respectively). When combined with atrial fibrillation, atrial flutter, hypertrophic cardiomyopathy, restrictive cardiomyopathy or valvular cardiomyopathy, intracardiac thrombus are mostly likely to occur in left atrium. Left cardiac thrombosis incidence rate increased with the decline of LVEF, increase of NYHA class and enlargement of cardiac chamber. Overall. the anticoagulation rate was 56.8%, warfarin was still the mainstay (45.1%) while non-vitamin K antagonist oral anticoagulants prescription rose year by year. As for imaging modalities for thrombus detection and diagnosis, transthoracic echocardiography was the most widely performed (75.1%). Conclusion: This study summarized underlying disease constitution, thrombus location and related factors, imaging modalities, and antithrombotic profile in HF patients with intracardiac thrombus comprehensively.